Immunogenicity and contraceptive efficacy of plant-produced putative mouse-specific contraceptive peptides - Ghasemian, Khadijeh; Broer, Inge; Schön, Jennifer; Kolp, Nadine; Killisch, Richard; Mikkat, Stefan; Huckauf, Jana (Frontiers in Plant Science, 2023)
Rodent population control through contraception requires species-specific oral contraceptive vaccines. Therefore, in this study, we produced putative mouse-specific contraceptive peptides, mZP2 (from oocyte) and mIzumo1 (from sperm), in plants using Agrobacterium-mediated transient expression. Peptides were produced separately in Nicotiana benthamiana using constructs encoding antigens containing three copies of each peptide. We also determined the immunogenicity and contraceptive effects of the plant-produced antigens in female BALB/c mice. Mice immunized subcutaneously with a relatively low amount of antigen (5 µg/dose of each peptide in a mixture) showed systemic immune responses against mZP2-3 and mIzumo1-3 antigens. Moreover, the mean litter size of mice treated with the plant-produced antigens was reduced by 39% compared to that of the control mice. Notably, there was a significant negative correlation between the number of pups born and individual antibody levels against both antigens. Immunofluorescence assays demonstrated the binding of induced antibodies to the oocytes of BALB/c and wild-type mice in vivo and in vitro, respectively. Our study demonstrate the feasibility of producing small contraceptive peptides in plants that can be further used to develop oral contraceptive vaccines against mouse populations.